PERANCANGAN APLIKASI INFORMASI TITIK GEMPA DI INDONESIA BERBASIS ANDROID - Cucut Susanto (SISFOTENIKA, 2013)
Abstract: Design of Earthquake Point Information Android-Base Application in Indonesia. Indonesia is a country located in the ring of fire or fire circle where an area often experience earthquakes and volcanic eruptions caused by the friction of the earth. This area is shaped like a horseshoe covers an area of 40,000 km long. Thus require an information about the rapid earthquake information and notifications directly in order to avoid things that are not desirable. For example, when the earthquake and tsunami in Aceh on Sunday morning, December 26, 2004. Magnitude 8.5 on the Richter scale resulted Approximately 500,000 lives lost in an instant around the edge of the world that is directly adjacent to the Indian Ocean. And Indonesia alone Approximately 126,000 casualties casualties. This is all due to the lack of information about earthquake faced. The purpose of this study is: to design an application that can provide location information where the latest quake which areas are affected by the earthquake by using mobile devices and can provide locations of seismic information can be viewed as Maps and Google Maps. The research method is the Data Collection Techniques to approach literature studies and experiments and observations.The results showed that the application provides a solution to the Indonesian public about the latest earthquake information, so that information is mobile earthquake can be accessed anytime and anywhere with the help of BMKG. Keywords: Design, Point Earthquake, Android.